The Effectiveness of Using International Phonetic Alphabet Symbols on Pronunciation Skills of Grade 12 Students - Caryll Dee Dumanggas; Uriel Uriel; Mike Jasper Otero; Jovenil (Eternal (English, Teaching, Learning & Research Journal))
The study entitled “The Effectiveness of Using International Phonetic Alphabet Symbols on Pronunciation Skills of Grade 12 Students” aimed to determine the effectiveness of using International Phonetic Alphabet Symbols on the pronunciation skills of Grade 12 students in UM Peñaplata College. The study used a quasi-experimental method as a research design. The essential data were gathered from a sample size of 24 respondents with the aid of a validated research-made questionnaire. Data were analyzed and interpreted using weighted mean and paired t-test as statistical tools. It was found that the Grade 12 students initially struggled with their English pronunciation skills; however, after the intervention, there was an increase in students' scores from the pre-test to the post-test. It was also found that there is a significant difference in the students' pronunciation skills before and after using the IPA symbols. The researchers acknowledged the major limitation, which is the absence of a control group during the study. Nevertheless, the implications of this study would be of interest to the curricularists and the education policymakers in integrating IPA symbols in English language classes.